2021
DOI: 10.21203/rs.3.rs-139636/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Related Factors of Dyslipidemia among Adults Aged 35 to 79 years in Southwest China

Abstract: This study aimed to investigate the prevalence of dyslipidemia and its related factors among adults aged 35 to 79 years in southwest China. From September 2013 to March 2014, a multi-stage, stratified sampling was conducted on 10221 people aged 35–79 years living in Chengdu and Chongqing by using the method of field questionnaire survey and measurement. The prevalence of high triglycerides (≥ 2.3 mmol/L), high total cholesterol (≥ 6.2 mmol/L), high low-density lipoprotein cholesterol (≥ 4.1 mmol/L), low high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[63] " mmol/L for TG among the participants. [64] Prevalence Adults Data from CHNS 2002, [65] China National Survey of Chronic Kidney Disease (CNSCKD) 2010, [66] CHNS 2011. [67] and Report on the Status of Nutrition and Chronic Diseases of Chinese Residents 2015 showed that the overall prevalence of dyslipidemia among Chinese adults aged ≥ 18 years increased dramatically.…”
Section: Journal Of Geriatric Cardiology Cardiovascular Health and Di...mentioning
confidence: 99%
See 2 more Smart Citations
“…[63] " mmol/L for TG among the participants. [64] Prevalence Adults Data from CHNS 2002, [65] China National Survey of Chronic Kidney Disease (CNSCKD) 2010, [66] CHNS 2011. [67] and Report on the Status of Nutrition and Chronic Diseases of Chinese Residents 2015 showed that the overall prevalence of dyslipidemia among Chinese adults aged ≥ 18 years increased dramatically.…”
Section: Journal Of Geriatric Cardiology Cardiovascular Health and Di...mentioning
confidence: 99%
“…Table 18 shows the prevalence of dyslipidemia among Chinese children in different regions. [64,83,84] [85] For the participants who had hypercholesterolemia, including high TC (≥ 6.22 mmol/L), high LDL-C (≥ 4.14 mmol/L), borderline high TC (5.18 ≤ TC < 6.21 mmol/L), or borderline high LDL-C (3.37 ≤ LDL-C < 4.14 mmol/L), or who reported using cholesterol-lowering drugs, the rates of awareness, treatment, and control were very low. This scenario was even worse in rural residents than urban citizens (Figure 24) and in women than in men (Figure 25).…”
Section: Journal Of Geriatric Cardiology Cardiovascular Health and Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the prevalence of sarcopenia in older people in Shanghai was 22.9%, and the ratio of male elderly individuals in Hong Kong was 9.4% [3] . Recently, some studies found that the prevalence of dyslipidemia in the elderly was 53.65%, and there was approximately 40% dyslipidemia globally [4] . Some studies have indicated that the association between sarcopenia and dyslipidemia is controversial.…”
Section: Introductionmentioning
confidence: 99%